Virtual exposure to natural versus urban environments: a pilot study on impacts on self-compassion, self-protection, and self-criticism - Dagmar Szitás; Júlia Halamová; Viliam Pichler (Scientific Reports)
Abstract This study explored the effects of a virtual forest environment compared to a virtual urban setting on key psychological factors, including self-compassion, self-protection, self-criticism, and stress. Designed as a pilot randomized controlled trial, the study included 28 adult participants who were randomly assigned to either the virtual forest or virtual city condition. Results from the Self-Compassion and Self-Criticism Scale indicated a significant increase in state self-compassion and a decrease in state self-criticism within the Forest Group. Notably, state self-criticism also decreased in the City Group. However, participants in the City Group experienced a significant increase in perceived stress and a decline in trait compassion, as measured by the Sussex-Oxford Compassion Scale. These findings suggest that virtual forest bathing may serve as a valuable therapeutic intervention, promoting self-compassion – recognized as a transdiagnostic factor for mental well-being – while reducing self-criticism, a known transdiagnostic factor of psychopathology.